2020
DOI: 10.1039/c9ob02381j
|View full text |Cite
|
Sign up to set email alerts
|

Branched lipid chains to prepare cationic amphiphiles producing hexagonal aggregates: supramolecular behavior and application to gene delivery

Abstract: Cationic amphiphiles featuring ramified lipid chains self-organized in water as inverted hexagonal aggregates. They demonstrated high gene delivery efficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This structural feature introduces a kink in the lipid chain that disturbs the lipid packing and increases fluidity, as previously reported [39]. In the case of branched lipid chains, the ramification results in a larger volume of hydrophobic chains that contribute to the formation of a cone-shaped amphiphilic structure that favors non-lamellar self-assemblies and produces efficient gene carriers [23]. Their synthesis starts with a transesterification reaction involving a lipid alcohol and diphenylphosphite.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…This structural feature introduces a kink in the lipid chain that disturbs the lipid packing and increases fluidity, as previously reported [39]. In the case of branched lipid chains, the ramification results in a larger volume of hydrophobic chains that contribute to the formation of a cone-shaped amphiphilic structure that favors non-lamellar self-assemblies and produces efficient gene carriers [23]. Their synthesis starts with a transesterification reaction involving a lipid alcohol and diphenylphosphite.…”
Section: Resultsmentioning
confidence: 66%
“…The synthesis of the new cationic lipids is depicted in Figure 2. Regarding the choice of the lipid chains, we selected oleyl chains or the branched lipid chain 2-decyl-tetradecanyl because they proved their efficacy when incorporated in the structure of other cationic amphiphiles [23,35]. Previous publications have indeed observed that oleyl chains increase the fluidity of self-assemblies thanks to the presence of their carbon-carbon double bond possessing a Z-configuration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations